A Study and Implementation of a Web-based Intelligent Employer Relation (s) Management System (ERMS) - Salisu Muhammad, Usman (2010)
In this Chapter , the author will perform a literature review to study and research on the current management practice of INTI’s employer relations department. The author will start his research by analyzing the overall of INTI’s ER department followed by the organizational structure of INTI’s ER. Last but not least, the author will also look into the problem that is faced in the current practice of INTI’s ER department. At the end of the chapter, the author hopes that he will be able to fully understand the activities carried out by INTI’s ER department.